Women and Pre‐Tenure Scholarly Productivity in International Studies: An Investigation into the Leaky Career Pipeline. Issue 4 (5th April 2013) - Hancock, Kathleen J.; Baum, Matthew A.; Breuning, Marijke
Abstract : Why are women still relatively scarce in the international studies profession? Although women have entered careers in international studies in increasing numbers, they represent increasingly smaller percentages as they move from PhD student to full professor. Our survey investigates why this is so, focusing on the assistant professor years, which are crucial to succeeding in the profession. We found that there are significant differences in publication rates, as well as differences in research focus (traditional subjects vs. newer subfields) and methodologies (quantitative vs. qualitative). Further, women and men have different perceptions of official and unwritten expectations for research, and policies regarding faculty with children may affect how successful women are in moving up the ladder. Taken together, these findings suggest reasons for the continued "leakiness" of the career pipeline for women and some potential solutions.